Petrographic characteristics of the granite gneisses of the Usmanskiy Pinewood forest: towards the origin of the “Kudeyarov stones” in the Voronezh State Nature Biosphere Reserve (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: The article presents the results of a study of the location of boulders within the territory of the “V. Peskov Voronezh State Nature Biosphere Reserve”. The studied boulders are found in a rather limited area, 8 kilometres north-west from the Central Homestead of the Reserve, on the slope of a fluvial terrace on the right bank of the Studenka River. The area is a swampy lowland not far from the riverbed. The boulders are granite gneisses of similar compositions. However, they differ in their size and degree of roundness. Some of the boulders are covered with grass and buried in the ground, which indicates that they have been at the site for a long time. Methodology: In order to preserve the natural objects, we took samples from the smallest boulder. We then prepared two projections of the transparent polished sections: one orthogonal to the gneiss texture direction and one in its plane. The sections were studied using an Olympus BS51 polarizing microscope. The composition of the rock-forming minerals was determined using a Jeol 6380 LV scanning electron microscope with an INCA 250 energy dispersive analysis system. Results and discussion: The microscopic study demonstrated that the rocks have a lepidogranoblastic structure. The rock-forming minerals are typical of granite gneisses and mainly include plagioclase, potassium feldspar, and quartz as well as fine-grained biotite aggregate, which forms characteristic intergrowths with feldspar and quartz. The study also determined the presence of accessory minerals (garnet, monazite, zircon, and ilmenite) as inclusions within other minerals. The petrographic composition and the interaction between the rock-forming minerals differ significantly from those of the known varieties of felsic rocks of the Voronezh Crystalline Massif. This, along with some other factors, allows the authors to suggest that the boulders are of anthropogenic origin. Conclusions: The characteristic petrographic features used for the determination of the boulders’ parent rocks were the following: a) presence of garnets, both as individual grains and in the form of large almandine aggregates; b) "spotted" rock texture due to elongated accumulations of pale yellow potassium feldspar; c) abundance of carbonate veins of various thickness; d) intergrowth of biotite and quartz.
Keywords: Kudeyarov stones; Voronezh Reserve; granite gneisses; East European platform